Effects of rumen‐protected methionine on milk production in early lactation dairy cattle fed with a diet containing 14.5% crude protein. (5th November 2018) - Tamura, Tetsuo; Inoue, Kazunori; Nishiki, Hideto; Sakata, Masafumi; Seki, Makoto; Koga, Teruaki; Ookubo, Yoshihiro; Akutsu, Kazuhiro; Sato, Say; Saitou, Kouichi; Shinohara, Hikari; Kuraisi, Terumi; et al.
Abstract: We evaluated the influence on milk production of feeding early lactation cows a diet that included 14.5% crude protein (CP) and that did not meet methionine (Met) requirements or that met them by supplying rumen‐protected Met (RPMet). Thirty‐nine multiparous Holstein cows were allocated into two groups. For 15 weeks after calving, each group was fed one of the two total mixed rations, Control ( n  =   20) or Treatment ( n  =   19). The Treatment group received added RPMet at 0.034% (8 g/day) of the Control diet on dry matter basis. The adequacies of Met for the Control and Treatment groups were 96% and 106%, respectively, and for other amino acids, >110%. The CP level (14.5%) was 1 percentage point lower than that recommended by the Japanese Feeding Standard (2006). No between‐group differences were found in milk yield (40 kg/day), milk composition, plasma profile, rumen fermentation, nitrogen balance, or cow health. Met intake and the amount of rumen‐undegradable feed Met were higher in the Treatment group ( p  <   0.05). Microbial Met and total metabolizable Met did not differ between groups. Supplying RPMet in a 14.5% CP diet during early lactation did not dramatically affect milk production, because the amount of total metabolizable Met was unchanged.